En-bloc resection of metastases of the proximal femur and reconstruction by modular arthroplasty is not only justified in patients with a curative treatment option: an observational study of a consecutive series of 45 patients - Bischel, Oliver E.; Höppchen, Arnold; Böhm, Paul M.; Lehner, Burkhard; Bitsch, Rudi G.; Seeger, Jörn Bengt (Journal of Clinical Medicine, 2020)
Background: There is little conformity regarding the surgical treatment of metastasis of the proximal femur, especially in palliative patients with limited life expectancy. Patients and Methods: En-bloc resection of secondary bone malignancies of the proximal femur and reconstruction by modular arthroplasty was performed in a consecutive series of 45 patients. The mean follow-up period was 16.4 months (0.6–74.7). Results: The survival rate of all patients was 6.6% (95% CI: 0–14.9) at 74.7 months. There was no significant difference in patients with a solitary or disseminated disease at index operation (log-rank p = 0.1214). Recurrent dislocation was the most frequent local complication (n = 6) necessitating an open reduction in four cases. The use of a Trevira tube showed a higher risk of dislocation compared to the simple bonding of remaining soft tissue (6 out of 28 vs. 0 out of 17; Fisher test: p = 0.0463). The worst-case survival rate with the removal of the arthroplasty for any cause and/or loss to follow-up was 80.0% (95% CI: 44.9–100) at 74.7 months (n = 1 due to low-grade infection). Conclusions: En-bloc resection of metastases and reconstruction by modular arthroplasty is reliable even in patients with very limited life expectancy. Local complications due to tumor growth or instability after intralesional surgery could be managed successfully but recurrent dislocation as the most frequent complication has to be taken into account. The simple bonding of remaining soft tissue around the prosthesis without the use of an attachment tube may reduce the dislocation rate and reoperation risk.